Comparative Stylistics of Welsh and English : Arddulleg y Gymraeg - Steve Morris (University of Wales Press, 2018)
Comparative stylistics is a technique for closely comparing the stylistic resources of two languages, in this case Welsh and English, to observe how each deploys its linguistic devices in ways that reflect its own characteristic idiom and expressive spirit and to invite the reader to practice the techniques examined. The book seeks to describe and lay out the various patterns than can be found in twentieth century Welsh, attempting to capture some of those linguistic devices which contribute to the flavour of idiomatic Welsh style, with a view to making such patterns known and available to writers for whom the English-like patterns may be the ones that come most readily to mind. The book is organised into eleven chapters.